2000
DOI: 10.1021/bi9924563
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies on Bioactive Compounds. 30. Crystal Structure and Molecular Modeling Studies on the Pneumocystis carinii Dihydrofolate Reductase Cofactor Complex with TAB, a Highly Selective Antifolate,,

Abstract: The crystal structure of the ternary complex of NADPH, the potent antifolate [2, 4-diamino-5-¿3-[3-(2-acetyloxyethyl)-3-benzyltriazen-1-yl]-4 -chloroph enyl¿-6-ethylpyrimidine] (TAB, 1) and Pneumocystis carinii dihydrofolate reductase (pcDHFR), refined to 2.1 A resolution, reveals that TAB binds similar to the antifolates trimethoprim and methotrexate. These data also reveal multiple conformations for the binding geometry of TAB with two preferred orientations of the acetyloxy and benzyl groups that results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…This allows RAB1 to more easily conform to the binding site. Ligand flexibility has previously been touted as a predictor of selectivity (17).…”
Section: Structure Of B Anthracis Dhfr-rab1 Complexmentioning
confidence: 99%
“…This allows RAB1 to more easily conform to the binding site. Ligand flexibility has previously been touted as a predictor of selectivity (17).…”
Section: Structure Of B Anthracis Dhfr-rab1 Complexmentioning
confidence: 99%
“…Despite this primary sequence difference, both DHFR enzymes showed similar K M values for dihydrofolate and NADPH and similar inhibition profiles with a variety of antifolate inhibitors. The crystal structure of the interaction of purified recombinant DHFR with antifolate compounds has been resolved, and domains important in the inhibitory activity of the compound have been identified (Cody et al, 2000). Correlation of structure-activity predictions with results of inhibitory studies of a wide array of DHFR inhibitors should lead to more potent and selective inhibitors of P. carinii (and specifically P. carinii f. sp.…”
Section: Biochemistry and Cell Biologymentioning
confidence: 99%
“…Since immunosuppressed patients and those with AIDS are severly affected by these pathogens, efforts have been focused on the design of antifolates that are selective against P. carinii DHFR (pc DHFR) and T. gondii (or tgDHFR) (12, 18, 22-24, 27, 28, 33, 42, 44, 48). In most of these studies, antifolate selectivity reported as a ratio of 50% inhibitory concentrations (IC 50 s) from two DHFR species was measured against crude DHFR preparations from rat liver (44,47,48).Evidence from sequence analysis and three-dimensional crystal structures of DHFR from many species shows that there is a high degree of conservation at the primary sequence and structural level among DHFRs (8,[10][11][12][13][14]17,19,29,34,36,37,41,43,50,53,55). However, kinetic and biochemical characterization data reveal differences in the mechanism of action that result in significant species specificity by selected inhibitors (15-17, 21, 25, 26, 31, 36, 39, 43).…”
mentioning
confidence: 99%
“…Evidence from sequence analysis and three-dimensional crystal structures of DHFR from many species shows that there is a high degree of conservation at the primary sequence and structural level among DHFRs (8,[10][11][12][13][14]17,19,29,34,36,37,41,43,50,53,55). However, kinetic and biochemical characterization data reveal differences in the mechanism of action that result in significant species specificity by selected inhibitors (15-17, 21, 25, 26, 31, 36, 39, 43).…”
mentioning
confidence: 99%
See 1 more Smart Citation